Konstitusionalitas Kebijakan Belanja Subsidi Bahan Bakar Minyak dalam Anggaran Pendapatan dan Belanja Negara - Abidin, M. Zainul (Jurnal Konstitusi, 2013)
The aims of  this  research  was  first,  examining  the  harmony  of  the  policy  of fuel subsidy in the State  Budget  Law  based  on  the  1945  Constitution  of  the Republic of Indonesia and second, observing the subsidy policy  can  be  taken under Article 33 and 34 of the Constitution. This research used the literature studies. Data obtained from literature studies  were  discriptively  and  qualitativly  analyzed  used  by  the  laws  and  public  finance   theories. It was concluded that the allocation policy of fuel subsidy in the budget in accordance with Article 23 paragraph (1) and Article 33 paragraph (3), ie in order to achieve maximum prosperity for the people. In the current situation, the policy of subsidized fuel does not accord the principle of efficiency with justice, continuity, and environmental perspective (Article 33, paragraph 4). Pursuant to Article 34 paragraph (1) and (2) Constitution, the subsidy policy should be focused to meet the needs of the poor / impoverished persons, inadequate and underprivileged.